Persistent of respiratory syncytial virus in human dendritic cells and influence of nitric oxide - Hobson, L (Blackwell Science Inc, 2008)
The annual epidemics of respiratory syncytial virus (RSV) infection are probably explained by poor herd immunity and the existence of a dormant reservoir of virus that is activated by an unknown trigger. The virus causes particular problems in infants, the elderly and patients with chronic obstructive airways disease (COPD). During two consecutive winters, human monocyte-derived dendritic cells (DCs) were exposed on a single occasion to one of two forms of RSV labelled with a fluorescent expresser genes (rgRSV or rrRSV) during the epidemic season. The cultures were maintained for many months, with fresh DCs being added at monthly intervals. The cultures were variously exposed to 600 parts per billion (ppb) nitric oxide for 15 min, nitric oxide (NO) donors and NO inhibitors outside the RSV epidemic season. The pattern of productive infection of DCs in vitro appeared to parallel the natural epidemics, in that DCs exhibited evidence of viral replication and productive infection only as manifested by intracellular fluorescence and infection of HeLa cells during the RSV epidemic season. When the long-term cultures were exposed to the above agents outside the RSV epidemic season there was again evidence of vigorous replication and productive infection, as shown by the reappearance of fluorescence and productive infection of HeLa cells. The results indicate that RSV may remain dormant in dendritic cells for prolonged periods and that replication appears to be activated by suppression of endogenous NO production. These observations may be key to our understanding of the mechanisms contributing to the annual epidemics of RSV infection.